CORRELATES OF BEING DIAGNOSED WITH ATTENTION DEFICIT HYPERACTIVE DISORDER IN UNDER 18 YEAR OLDS - UNITED STATES - Shaikh, Masood Ali; Shaikh, Irshad Ali (Journal of Ayub Medical College Abbottabad, 2006)
Attention Deficit Hyperactive Disorder (ADHD) is characterized by inattention, hyperactivity and impulsiveness1. Learning disabilities have been reported in up to 30% of children with this disorder2. Annually some $3.3 billions are spent on its healthcare cost in the United States3. We describe gender, race, poverty level and educational attainment in the family associated with ADHD in under-eighteen year old children in the United States of America, using data from the National Survey of Children's Health, 2003 (NSCH)4. The NSCH was conducted from January 2003 to July 2004; by the National Center for Health Statistics, and funded by the Maternal and Child Health Bureau of the Health Resources and Services Administration. NSCH was designed to produce national and statespecific estimates, using random-digit-dial sample of households with under-18 children. The respondent was either the parent or a family member of the child, and interviews were conducted using a computerassisted telephone interviewing system. Affirmative response to the question Has a doctor or health professional ever told you that the child has Attention Deficit or Attention Deficit Hyperactive Disorder that is ADD or ADHD? was used to identify ADHD cases. Design-based analysis with STATA release 9.1 was done using Logistic Regression, and Odds Ratios (OR) were computed for the association of ADHD, with various socio-demographic variables; data was downloaded from the website of National Center For Health Statistics4. The overall prevalence of ADHD was 6.8% with 95% Confidence Interval (CI) 6.5% - 7.1% (n = 90226). In males prevalence was 9.6% (95% CI 9.1% - 10.1%), while in females it was 4.0% (95% CI 3.6% - 4.2%). Compared to males, females were much less likely to be diagnosed with ADHD (OR 0.36, 95% CI 0.33 - 0.40). Race was assessed in the categories of White, Black, Multiple and Other. Compared to Whites, Black children were less likely to be diagnosed with ADHD (OR 0.79, 95% CI 0.68 - 0.92) as well as children in the Other racial group (OR 0.45, 95% CI 0.32 - 0.64), while no statistically significant association found with Multiple race. Highest level of education attained by anyone in a house of the child was assessed in terms of less than high school, high school, and more than high school educational attainment. No statistically significant association was found with educational attainment and a child in the family diagnosed with ADHD. Poverty level of the household was assessed in three categories; less than 150%, 150% to less than 300%, and 300% plus, based on Department of Health and Human Services guidelines. Compared to children in households with the base category of less than 150% poverty level, children in the 150% to less than 300% and 300% plus category were less to be diagnosed with ADHD; i.e. (OR 0.79, 95% CI 0.69 - 0.90) and (OR 0.65, 95% CI 0.57 - 0.74), respectively. In conclusion, male children were more likely, while children in families living in 150% or above poverty levels were less likely to have been told by a doctor or health professional that they have Attention Deficit or Attention Deficit Hyperactive Disorder.